A Fully Integrated 2:1 Self-Oscillating Switched-Capacitor DC–DC Converter in 28 nm UTBB FD-SOI - Matthew Turnquist; Markus Hiienkari; Jani Mäkipää; Lauri Koskinen (Journal of Low Power Electronics and Applications, 2016)
The importance of energy-constrained processors continues to grow especially for ultra-portable sensor-based platforms for the Internet-of-Things (IoT). Processors for these IoT applications primarily operate at near-threshold (NT) voltages and have multiple power modes. Achieving high conversion efficiency within the DC–DC converter that supplies these processors is critical since energy consumption of the DC–DC/processor system is proportional to the DC–DC converter efficiency. The DC–DC converter must maintain high efficiency over a large load range generated from the multiple power modes of the processor. This paper presents a fully integrated step-down self-oscillating switched-capacitor DC–DC converter that is capable of meeting these challenges. The area of the converter is 0.0104 mm2 and is designed in 28 nm ultra-thin body and buried oxide fully-depleted SOI (UTBB FD-SOI). Back-gate biasing within FD-SOI is utilized to increase the load power range of the converter. With an input of 1 V and output of 460 mV, measurements of the converter show a minimum efficiency of 75% for 79 nW to 200 µW loads. Measurements with an off-chip NT processor load show efficiency up to 86%. The converter’s large load power range and high efficiency make it an excellent fit for energy-constrained processors.